Radiatively induced Lorentz and CPT violation in Schwinger constant field approximation - Chaichian, M. (2014)
The Schwinger proper-time method is an effective calculation method, explicitly gauge-invariant and nonperturbative. We make use of this method to investigate the radiatively induced Lorentz- and CPT-violating effects in quantum electrodynamics when an axial-vector interaction term is introduced in the fermionic sector. The induced Lorentz- and CPT-violating Chern-Simons term coincides with the one obtained using a covariant derivative expansion but differs from the result usually obtained in other regularization schemes. A possible ambiguity in the approach is also discussed. (C) 2001 Published by Elsevier Science B.V.